Prescription drug use and abuse. - Meadows M (FDA Consumer)
It was supposed to be a short course of treatment with tranquilizers after the death of her infant son 15 years ago. But Lynn Ray, 46, of Germantown, Md., says her abuse of the anti-anxiety drug Xanax and other prescription drugs led to a long struggle with addiction that nearly ruined her life.